Optical clearing: an alternative sample preparation method for propagation based phase contrast μCT - Sagar, Md Motiur Rahman; Svetlove, Angelika; D’Amico, Lorenzo; Pinkert-Leetsch, Diana; Missbach-Guentner, Jeannine; Longo, Elena; Tromba, Giuliana; Bohnenberger, Hanibal; Alves, Frauke; Dullin, Christian (Frontiers in physics, 2024)
Synchrotron radiation propagation-based phase-contrast micro-computed tomography (SRμCT) has been used increasingly for detailed characterization of tissue specimens, alternative to classical histology. It allows rapid and non-destructive three-dimensional (3D) virtual histology of unstained specimens. Although many studies show that standard protocols for formalin-fixation and paraffin-embedded (FFPE) tissue specimens are well suited for propagation based phase-contrast imaging (PBI), refinement of sample preparation protocols for this relatively recent development is still in its early stage. There are several limitations using FFPE blocks including air-bubble inclusion, and crack formation, which affect the quality of the micro-CT scans. In this study we demonstrate that optical clearing of colon cancer specimen followed by embedding in Phytagel, as an alternative sample preparation protocol yields comparable PBI micro-CT image quality and mitigates the aforementioned drawbacks of FFPE specimens. Moreover, since single-distance phase retrieval algorithms for PBI image reconstruction expect scanned materials to be either weakly-absorbing or having a fixed ratio between absorption and phase shift, we hypothesize that optical clearing will result in specimens that are well in line with these mathematical assumption of the applied phase retrieval algorithm (homogeneous form of the Transport-of-Intensity equation TIE-HOM). In addition, we show that classical histological analysis is still possible after re-embedding of the specimen in paraffin. Thus, the proposed novel workflow to scan optical cleared specimens using SRμCT can be used in combination with light sheet microscopy and can be integrated in a classical pipeline for pathological tissue characterization.